The Implementation of Padlet to Foster EFL Students’ Achievement in Writing - Muh. Farid Sehuddin; Nurdin Noni; Baso Jabu (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
This study is the quasi experimental research that aimed to know the effect of the implementation of Padlet to the students’ achievement in writing. The implementation Padlet as independent variables and the students’ achievement in writing as a dependent variable. The population in this research is all students class XI MIA MAN 1 Makassar that consist of eight classes. Class XI MIA 5 as a control group that consist of 30 students and class XI MIA 1 as an experiment group that consist of 30 students. The data of the research was obtained by the study results test on the subject of the velocity reaction for pre-test and post-test. The data was analyzed by writing test. Based on analysis of inferential statistics for writing achievement, the P = 0.001, and it less than  = 0,05 was obtained, it is means that the implementation Padlet is significantly influence to the students’ achievement in writing of the students’ class XI MIA 1 MAN I Makassar on the material subject of writing.